Coinhibitory Molecules in Autoimmune Diseases - Norihiko Watanabe; Hiroshi Nakajima (Clinical and Developmental Immunology)
Coinhibitory molecules such as CTLA-4, PD-1 and BTLA negatively regulate immune responses. Multiple studies indicate that the deficiency or mutation of coinhibitory molecules leads to the development of autoimmune diseases in mice and humans, indicating that the negative signals from coinhibitory molecules are crucial for the prevention of autoimmunity. In some conditions, the administration of decoy coinhibitory receptors (e.g., CTLA-4 Ig) or mAb against coinhibitory molecules suppresses the responses of self-reactive T cells in autoimmune diseases. Therefore, modulation of coinhibitory signals seems to be an attractive approach to induce tolerance in autoimmune diseases in humans where the disease-inducing self-antigens are not known. Particularly, administration of CTLA-4 Ig has shown great promise in animal models of autoimmune diseases and has been gaining increasing attention in clinical investigation in several autoimmune diseases in humans.